2022
DOI: 10.24114/js.v6i2.33371
|View full text |Cite
|
Sign up to set email alerts
|

Apakah Learning Loss Berpengaruh Terhadap Kemampuan Numerasi Siswa?

Abstract: The pandemic has the potential to cause learning loss. This study aims to determine students' numeracy skills during the pandemic. The indicator of numeracy ability in this study is the students' ability to solve basic arithmetic operations. The type of research used is survey research. Data collection using test instruments. The research subjects were 110 elementary school students. Data were analyzed using descriptive statistics. The data is presented in the form of tables and diagrams. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Menurut Andreas dalam (Siskawati et al, 2021) kemampuan numerasi yang baik nantinya akan menjadi proteksi terbaik terhadap angka pengangguran, penghasilan rendah, dan kesehatan yang buruk. Hal yang lebih mendasar seperti pernyataan Mahmud dan Pratiwi dalam (Widodo & Umar, 2022) bahwa kemampuan numerasi merupakan bekal bagi peserta didik dalam mengembangkan pengetahuan dan keterampilan di sekolah. Kemampuan numerasi menjadi kemampuan yang penting dikembangkan di sekolah mengingat terjadinya learning loss pada pembelajaran selama pandemi Covid-19 (Maulyda et al, 2021).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Menurut Andreas dalam (Siskawati et al, 2021) kemampuan numerasi yang baik nantinya akan menjadi proteksi terbaik terhadap angka pengangguran, penghasilan rendah, dan kesehatan yang buruk. Hal yang lebih mendasar seperti pernyataan Mahmud dan Pratiwi dalam (Widodo & Umar, 2022) bahwa kemampuan numerasi merupakan bekal bagi peserta didik dalam mengembangkan pengetahuan dan keterampilan di sekolah. Kemampuan numerasi menjadi kemampuan yang penting dikembangkan di sekolah mengingat terjadinya learning loss pada pembelajaran selama pandemi Covid-19 (Maulyda et al, 2021).…”
Section: Pendahuluanunclassified
“…Terjadinya learning loss berdampak salah satunya pada aspek kognitif siswa SD yaitu kemampuan membaca dan matematika (Musoffa, 2022). Penelitian (Widodo & Umar, 2022) mempertegas bahwa menurunnya kemampuan numerasi siswa di sekolah dasar salah satunya merupakan akibat dari learning loss. Dilansir dari berita (Kemendikbudristek, 2021) learning loss terjadi pada aspek literasi dan numerasi, di mana terjadi penurunan tingkat literasi pada kelas 1 sama dengan 6 bulan dan tingkat penurunan numerasi sama dengan 5 bulan.…”
Section: Pendahuluanunclassified
“…The negative impact of learning loss was proven by a research conducted in 2022 which showed learning loss resulted in a decrease of student's numeric skills [3]. Besides that, school closure or other factors resulting in a flawed learning process and learning loss, the consequences are students will find it hard to find jobs in the market field and there will be a decrease in the quality of human resource hence increases poverty rate [4]. Learning loss happens more often in mathematics than in other subjects [5].…”
Section: Introductionmentioning
confidence: 99%